PLASMA CHARACTERISTICS IN SQUARE PULSE ARC DISCHARGE OF PLASMA CATHODE ELECTRON SOURCE DEVICE - Agus Purwadi; Bambang Siswanto; Wirjoadi .; Lely Susita R.M.; Sudjatmoko . (GANENDRA Majalah IPTEK Nuklir, 2013)
Plasma parameters in Plasma Cathode Electron Source Device (PCESD) are very important things because they will determine the eficiency of its electron extraction. Square pulse mode of PCESD’s arc discharge plasma current can be obtained by using Pulse Forming Network (PFN) circuits which is called Arc Discharge Power Supply (ADPS). The square pulse mode is necessity to simplify in electron irradiation dose calculation. ADPS is connected with Hollow Anode Chamber (HAC) which is placed inside of PCESD to produce arc discharge plasma. The value of arc discharge plasma current is the main key to determine plasma parameters that can be measured by using Rogowski coil. The value of the arc discharge plasma current is IADPS = 206.30 A with pulse width  = 80 μs. Whereas the plasma parameters values inside of the HAC are: the electron plasma density ne = (16.85  1019) m-3, electron plasma temperature Te = 2.609 eV, electron plasma frequency fe = 116.74 GHz, and Debye length λD = 9.958 µm respectively.